2010
DOI: 10.1155/2010/642420
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Model of Human Erythrocytes: Practical Application of the E-Cell Simulation Environment

Abstract: The human red blood cell (RBC) has long been used for modeling of complex biological networks, for elucidation of a wide variety of dynamic phenomena, and for understanding the fundamental topology of metabolic pathways. Here, we introduce our recent work on an RBC metabolic model using the E-Cell Simulation Environment. The model is sufficiently detailed to predict the temporal hypoxic response of each metabolite and, at the same time, successfully integrates modulation of metabolism and of the oxygen transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Alternatively, Yoshida and colleagues and Zolla and colleagues have independently proposed anaerobic storage of RBCs as a strategy to exploit the above‐mentioned oxygen‐dependent metabolic modulation phenomenon in RBCs to promote energy metabolism, while concomitantly removing a key contributor to pro‐oxidant reactions. Metabolomics studies have been performed to confirm that energy metabolism‐related variables are improved by anaerobic storage at the expense of the pentose phosphate pathway and general antioxidant potential, consistent with previous in vitro studies . More recently, we demonstrated a role for anaerobiosis versus anaerobiosis in presence of CO 2 in modulating metabolic responses upon deoxygenation (Fig.…”
Section: Descriptive Metabolomics In Design and Testing Of Transfusiosupporting
confidence: 88%
“…Alternatively, Yoshida and colleagues and Zolla and colleagues have independently proposed anaerobic storage of RBCs as a strategy to exploit the above‐mentioned oxygen‐dependent metabolic modulation phenomenon in RBCs to promote energy metabolism, while concomitantly removing a key contributor to pro‐oxidant reactions. Metabolomics studies have been performed to confirm that energy metabolism‐related variables are improved by anaerobic storage at the expense of the pentose phosphate pathway and general antioxidant potential, consistent with previous in vitro studies . More recently, we demonstrated a role for anaerobiosis versus anaerobiosis in presence of CO 2 in modulating metabolic responses upon deoxygenation (Fig.…”
Section: Descriptive Metabolomics In Design and Testing Of Transfusiosupporting
confidence: 88%
“…2629 According to this model, 2629 as much as 92% of glucose is catabolized through the classic Embden-Meyerhoff glycolytic pathway under normoxia, while anoxia triggers consumption of as much as 90% of glucose via the PPP. This model has been supported by in vitro evidence 30 and in silico prediction based on metabolomics data of ex vivo aging RBCs under anaerobic conditions 31,32 . However, evidence of in vivo RBC metabolic adaptations to hypoxia has not been hitherto produced.…”
Section: Introductionmentioning
confidence: 73%
“…19 Previous metabolomics studies on anaerobically stored RBCs showed limited or no effect of anaerobic storage on glutathione homeostasis, 6 as we confirmed in all arms of this study. At the same time, previous dynamic in silico simulations 20 and actual metabolomics assessment 6 of RBC responses to hypoxia had documented significant beneficial effects of anaerobic storage on energy metabolism. Previously, we observed that anaerobically stored RBC units consistently have significant improvements in ATP and DPG levels as well as an increased 24-hour recovery compared to the control stored under standard aerobic storage conditions.…”
Section: Discussionmentioning
confidence: 95%